New-Generation Graphene from Electrochemical Approaches: Production and Applications - Yang, Sheng; Lohe, Martin R.; Muellen, Klaus; Feng, Xinliang (Advanced Materials, 2016)
Extensive research suggests a bright future for the graphene market. However, for a long time there has been a huge gap between laboratory-scale research and commercial application due to the challenging task of reproducible bulk production of high-quality graphene at low cost. Electrochemical exfoliation of graphite has emerged as a promising wet chemical method with advantages such as upscalability, solution processability and eco-friendliness. Recent progress in the electrochemical exfoliation of graphite and prospects for the application of exfoliated graphene, mainly in the fields of composites, electronics, energy storage and conversion are discussed.
CRIS-Team Scopus Importer:2023-03-20
Keywords: 2D materials; electrochemical exfoliation; electronic devices; graphene; integrated composites